2018
DOI: 10.1186/s13014-018-1108-9
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal organ position variation in children during image-guided radiotherapy

Abstract: BackgroundInterfractional organ position variation might differ for abdominal organs and this could have consequences for defining safety margins. Therefore, the purpose of this study is to quantify interfractional position variations of abdominal organs in children in order to investigate possible correlations between abdominal organs and determine whether position variation is location-dependent.MethodsFor 20 children (2.2–17.8 years), we retrospectively analyzed 113 CBCTs acquired during the treatment cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Our results also show that variation in DR differences increased with more caudal organ location. This is in agreement with results of Huijskens et al., who found in paediatric cancer patients that position variation of the ipsilateral diaphragm was more representative for position variations of the liver and spleen than for kidney position variations 35 . Additionally, we observed differences in DR within volunteers, that is, between PBHs of individual volunteers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also show that variation in DR differences increased with more caudal organ location. This is in agreement with results of Huijskens et al., who found in paediatric cancer patients that position variation of the ipsilateral diaphragm was more representative for position variations of the liver and spleen than for kidney position variations 35 . Additionally, we observed differences in DR within volunteers, that is, between PBHs of individual volunteers.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with results of Huijskens et al, who found in paediatric cancer patients that position variation of the ipsilateral diaphragm was more representative for position variations of the liver and spleen than for kidney position variations. 35 Additionally, we observed differences in DR within volunteers, that is, between PBHs of individual volunteers. It has been previously reported that respiratory patterns may change during radiation therapy, 36 however the drift of the RHT and all organs is linear throughout the PBH with constant velocity.…”
Section: Discussionmentioning
confidence: 68%
“…Various 4D CT, 4D MRI, and CBCT techniques have been used to measure pediatric tumor and organ motion. [48][49][50][51] As commercial 4D CT was designed primarily for adult patients with lung cancer, the scan parameters and pressure bellows need to be modified for children. Studies have found that the extent of respiration-induced motion is smaller in younger children than in older individuals, but that this motion can approach or exceed 1 cm for the diaphragm, spleen, kidney, and some tumors of adolescents.…”
Section: Image-guided Patient Positioning Motion Management and Adapt...mentioning
confidence: 99%
“…This is particularly relevant when treating pediatric patients with neuroblastoma, HL, hepatoblastoma, Wilms tumor, chest wall sarcoma, or tumors near the diaphragm. Various 4D CT, 4D MRI, and CBCT techniques have been used to measure pediatric tumor and organ motion 48‐51 . As commercial 4D CT was designed primarily for adult patients with lung cancer, the scan parameters and pressure bellows need to be modified for children.…”
Section: Image‐guided Patient Positioning Motion Management and Adapt...mentioning
confidence: 99%
“…Setup uncertainties have been extensively studied in photon radiotherapy for various treatment sites [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Lately, proton radiotherapy has emerged as a prominent alternative to photon therapy for pediatric CSI and today, both treatment modalities are relevant when studying residual errors and uncertainties.…”
Section: Introductionmentioning
confidence: 99%